Patellar Chondromalacia in Basketball Athletes: A Narrative Review of Epidemiology, Mechanisms, Assessment, and Management - Shiqi Tian (International Journal of Education and Humanities, 2026)
Patellar chondromalacia is a common patellofemoral disorder affecting young, highly active individuals, particularly basketball players who are frequently exposed to repetitive jumping, cutting, landing, and deep knee flexion. The substantial cumulative load on the patellofemoral joint increases this population's risk of symptomatic and asymptomatic cartilage degeneration, which may impair athletic performance and long-term joint health. This review aims to synthesize current evidence regarding the epidemiology, pathomechanics, clinical presentation, assessment, and management of patellar chondromalacia in basketball athletes. A narrative review approach was employed, analyzing recent and relevant scientific literature, including epidemiological studies, magnetic resonance imaging (MRI) findings, and clinical guidelines on patellofemoral disorders in athletic populations. The findings indicate a high prevalence of patellofemoral cartilage abnormalities among basketball players, as detected through MRI, even in asymptomatic individuals. Key contributing factors include repetitive mechanical overload, joint malalignment, neuromuscular deficits, quadriceps dysfunction, and inadequate management of training load. Accurate diagnosis requires an integrated approach that combines symptom assessment, physical examination, functional testing, and the selective use of imaging modalities. Conservative management remains the first-line treatment, emphasizing patient education, load modification, and combined hip- and knee-focused exercise therapy, with adjunctive interventions such as taping, foot orthoses, or manual therapy applied selectively. Early identification and individualized rehabilitation strategies are essential to mitigate symptom persistence, prevent progression of cartilage degeneration, and support sustained athletic performance in basketball players